PENGARUH BERMAIN KONSTRUKSI (LEGO) TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA PRASEKOLAH - Devita, Yeni (Jurnal Keperawatan Priority, 2018)
The development of fine motor is one of the factors determining the smoothness of the learning process both in the field of knowledge, as well as skills. Therefore, motor development greatly supports the success of learners learn. According to UNICEF in 2011 found 27.5 % or 3 million children experiencing disruption of fine motor development. In TK Raudhatul Jannah of 25 children there are 13 children have delays in fine motor development. If there is a disruption of fine motor development will lead to impaired concentration and learning difficulties. One of the games that can improve the smooth motor development is playing construction (lego). The game of construction (lego) can train eye and hand coordination. The purpose of this study to determine how the influence of playing construction (lego) to the smooth motor development of preschoolers. This research was conducted on 22 preschool children at TK Raudhatul Jannah Village Of Pangkalan Panduk Sub District Of Kerumutan Pelalawan with technique total sampling. This type of research is quantitative with quasi experimental design pre and post test without control. The analysis used to see the effects of play construction (lego) to the development fine motor at preschool children by using the paired samples t test and obtained the result of fine motor average value pretest 7.05 posttest 9.45 with an average increase 2.4. Paired samples t test result p value = 0.000 < α 5 % (p value < 0.05) the conclusion of this study there the effect of play construction (lego) to the development fine motor at preschool children in TK Raudhatul Jannah Village Of Pangkalan Panduk Sub District Of Kerumutan Pelalawan. It is expected that the community and parents always do stimulate the development of children according to the age stage of the child, so that children develop according to the stage of age.